2018 IEEE Energy Conversion Congress and Exposition (ECCE) 2018
DOI: 10.1109/ecce.2018.8557354
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of Gate-Oxide Degradation in Silicon Carbide MOSFETs

Abstract: Gate oxide degradation is more critical in Silicon-Carbide (SiC) MOSFETs than in Silicon (Si) MOSFETs. This is because of the smaller gate oxide thickness and the higher electric field that develops across the gate oxide in SiC MOSFETs. While multiple precursors have been identified for monitoring the gate oxide degradation in Si MOSFETs, very few precursors have been identified for SiC MOSFETs. The purpose of this paper is to demonstrate that gate oxide degradation precursors used in Si MOSFETs: a) threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In the case of encapsulated power semiconductors (power MOSFETs, diodes, IGBTs, etc.) the main stressors are maximum junction temperature [14], temperature swing during a single thermal cycle [15], blocking voltage [16], relative humidity [17] and gate voltage [18]. Each of these stressors accelerate at least one of the following failure modes, which are typical for encapsulated power semiconductors: solder delamination, solder joint fatigue, bond wire lift-off [19], bond wire heel-cracking [20], brittle cracking [21], corrosion [22], gate oxide time dependent breakdown [23], single event effects [24], etc.…”
Section: Accelerated Life Test Methodologymentioning
confidence: 99%
“…In the case of encapsulated power semiconductors (power MOSFETs, diodes, IGBTs, etc.) the main stressors are maximum junction temperature [14], temperature swing during a single thermal cycle [15], blocking voltage [16], relative humidity [17] and gate voltage [18]. Each of these stressors accelerate at least one of the following failure modes, which are typical for encapsulated power semiconductors: solder delamination, solder joint fatigue, bond wire lift-off [19], bond wire heel-cracking [20], brittle cracking [21], corrosion [22], gate oxide time dependent breakdown [23], single event effects [24], etc.…”
Section: Accelerated Life Test Methodologymentioning
confidence: 99%
“…Most of these works focused on the static parameters including threshold voltage (V th ), drain-source on-resistance (R DS ,on ), gate leakage current (I GSS ), drain leakage current (I DSS ) and et al [24][25][26][27][28][29], which are normally measured off-line using the semiconductor analyzer like Keysight B1505. Considering the fact that the SiC MOS-FET is used as the switch in the power converter, the dynamic parameters like gate charge (Q g ) [24], Miller plateau voltage (V g p ) [30,31], and switching transition [32] are more practical to be acquired. However, only few works have been conducted on the on-line monitoring circuit of SiC MOSFET using the dynamic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[24–29], which are normally measured off‐line using the semiconductor analyzer like Keysight B1505. Considering the fact that the SiC MOSFET is used as the switch in the power converter, the dynamic parameters like gate charge (Qg$ Q_g$) [24], Miller plateau voltage (Vgp$ V_{gp}$) [30, 31], and switching transition [32] are more practical to be acquired. However, only few works have been conducted on the on‐line monitoring circuit of SiC MOSFET using the dynamic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various studies on BTI in SiC MOSFETs [8][9][10][11][12][13][14][15][16][17]. It has widely been reported that VTH recovery occurs after stress removal [8,18,19].…”
Section: Introductionmentioning
confidence: 99%